COVID-19 pandemic and the challenges for urban informal sector: An insight from street vendors of the district Srinagar, Kashmir - Najar Shabir Ahmad; Bashir Aadil; Manzoor Shazia; Khan Bilal Ahmad; Sheikh Bisma Farooq (Temida)
This paper aims at presenting the findings of the study on the position of street vendors in the District Srinagar, Kashmir, in India, including both men and women, during the COVID-19 lockdown. The purpose of the study was to explore various challenges street vendors faced during the COVID-19 lockdown and to highlight the vulnerability of this particular group of informal workers. The data was collected through face-to-face interviews with the use of a questionnaire, on a sample of 150 street vendors from the District Srinagar. In addition, a certain number of in-depth interviews with selected respondents from the sample was done. The study findings show that the majority of the respondents have lost their job during the peak period of COVID-19, i.e. from March to July 2020. The findings have also revealed that the lockdown directly impacted the socio-economic conditions of the workers which made it very difficult for them to survive during the peak of COVID-19. Additionally, workers were struggling very hard in order to fulfill the basic daily needs of their families. Therefore, it is suggested that the government of India should provide financial support to street vendors in order to compensate for the loss caused due to the COVID-19 lockdown.